Classical theism and Buddhism: connecting metaphysical and ethical systems - McNabb, Tyler Dalton; Baldwin, Erik Daniel (Bloomsbury Academic, 2022)
"As an atheistic religious tradition, Buddhism conventionally stands in opposition to Christianity, and any bridge between them is considered to be riddled with contradictory beliefs on God the creator, salvific power and the afterlife. But what if a Buddhist could also be a Classical Theist? Showing how the various contradictions are not as fundamental as commonly thought, Tyler Dalton McNabb and Erik Baldwin challenge existing assumptions and argue that Classical Theism is, in fact, compatible with Buddhism. They draw parallels between the metaphysical doctrines of both traditions, synthesize their ethical and soteriological commitments and demonstrate that the Theist can interpret the Buddhist's religious experiences, specifically those of emptiness, as veridical, without denying any core doctrine of Classical Theism. By establishing that a synthesis of the two traditions is plausible, this book provides a bold, fresh perspective on the philosophy of religion and reinvigorates philosophical debates between Buddhism and Christianity"--
Keywords: Buddhism; Comparative studies; Relations Theism; Theism

Epidemic analytics for decision supports in COVID19 crisis - Lobo Marques, Joao Alexandre; Fong, Simon (Springer, 2022)
Covid-19 has hit the world unprepared, as the deadliest pandemic of the century. Governments and authorities, as leaders and decision makers fighting against the virus, enormously tap on the power of AI and its data analytics models for urgent decision supports at the greatest efforts, ever seen from human history. This book showcases a collection of important data analytics models that were used during the epidemic, and discusses and compares their efficacy and limitations. Readers who from both healthcare industries and academia can gain unique insights on how data analytics models were designed and applied on epidemic data. Taking Covid-19 as a case study, readers especially those who are working in similar fields, would be better prepared in case a new wave of virus epidemic may arise again in the near future.

Interaction design for a contemporary learning and teaching environment: promoting independent learning at the primary level - Chan, Ka Chi (USJ Theses and Dissertations, 2022)
The world is perpetually changing, and the COVID-19 pandemic has taught us that the future is full of unforeseen challenges and potentialities. What are the implications of the advancement in technology on education? How are teachers coping with contemporary educational expectations? Is there a need to redesign the learning environment? What is the exact nature of the forces driving such a change? Is there anything we can learn from successful innovations around the globe? The goals of this dissertation include designing a learning/teaching app and redesigning classroom furniture for primary-level education. A design thinking methodology is used, working through the phases of empathizing, defining, ideating, prototyping and testing the two potential designs
Keywords: Design; Interaction analysis in education; Interactive multimedia

Jornalismo e Qualidade no Mundo de Expressão Portuguesa - Camponez, Carlos; Simões, José Manuel; Christofoletti, Rogério (University of Saint Joseph, 2022)
"Jornalismo e Qualidade no Mundo de Expressão Portuguesa"propõe uma análise sobre a paisagem do jornalismo nos oitopaíses de língua oficial portuguesa - Portugal, Angola, Brasil, Cabo Verde, Moçambique, Guiné-Bissau, São Tomé e Príncipee Timor-Leste - e na Região Autónoma Especial de Macau. Olivro é uma reflexão sobre a legislação, o plano jurídico-constitucionalque enquadra os media no espaço lusófono, os contextosde mercado, as especificidades inscritas em fatoreshistóricos e económicos, em percursos políticos, bem comosobre as relações entre os media e os jornalistas e estes e opoder regulador do Estado.Os trabalhos reunidos nesta obra escrita por autores que partilhamentre si um dos idiomas mais falados do planeta, mostram as diferentes realidades do jornalismo no espaço dalíngua portuguesa, nomeadamente as suas redes de conhecimento, de empenho na promoção da qualidade da informação, de intercompreensão entre povos e culturas, de novas einovadoras formas de parcerias sociais com vista à partilha e àconstrução de mundividências.

Replication research in education: a guide to designing, conducting and analysing studies - Morrison, Keith (Routledge, 2022)
"Providing an overview of key issues in theory and practice, Replication Research in Education is designed to identify and discuss the benefits and challenges facing replication studies in education. Both clear and practical, this ground-breaking volume covers how to introduce, develop, conduct, report and discuss these studies, and the issues they raise for policy and practice. Bridging theory and practice, this book considers what replication research should look like, how it should be conducted and how to judge when it has been successful. It enables researchers to plan and conduct studies successfully, from their earliest stages through to completion. This key text: brings together in a single volume, existing issues, claims and counter-claims, discourses and practices of replication introduces, covers, and extends this field of research, indicating its possibilities and limits expands and adds to existing discussions and practices will enable researchers to design, conduct, evaluate and critique studies. The comprehensive and exhaustive coverage of issues and practices within Replication Research in Education make it a "must read" for all novice and experienced educational researchers who are considering, conducting, and reviewing replication studies in education"--

Succession in Chinese family business: transgenerational transmission of social capital in Macao - Phillips, Jenny O. L. (USJ Theses and Dissertations, 2022)
Macao is well known for its gaming industry. However, there are also many traditional small-to-medium enterprises which are family-owned and run. There is no doubt that social capital is one of the key competitive advantages that family businesses possess, particularly when it comes to Chinese businesses with strong family values that emphasize the importance of trustworthiness and guanxi (relationships). As opposed to other forms of capital, social capital cannot be passed from one generation to another through the will of the incumbents. So, how is social capital passed on in family businesses from one generation to the next? Based on an in-depth study of five cases of successful family businesses in Macao, this research identified the forms of social capital present in business families and the succession process of these firms. From the generalizations drawn from the five cases, a theoretical framework is proposed to understand the intergenerational transmission of social capital in Chinese family businesses
Keywords: China Macau (Special Administrative Region); Family-owned business enterprises

《學會閱讀》叢書第一輯 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

《學會閱讀》叢書第二輯 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文兒歌集 -- 果子級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 -- 果子級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 -- 花兒級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 -- 葉芽級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)